Efektivitas Latihan Peregangan Perut dan Kompres Hangat Terhadap Nyeri Disminore pada Remaja Putri Kelas XI dI MTS Tanwiriyyah Cianjur Tahun 2022 - Sulis Nuraeni; Marisca Agustina; Rina Afrina (JURNAL KEPERAWATAN SISTHANA, 2023)
This study aims to determine the effect of the effectiveness of abdominal stretching exercises and warm compresses on dysmenorrhea pain in young women at MTS Tanwiriyyah Cianjur in 2022. Young women often experience pain during menstruation (menstruation), causing discomfort, especially in daily activities. This complaint is not very good for adolescent development. By using non-pharmacological treatment, namely abdominal stretching exercises and warm compresses for dysmenorrhea pain, it can reduce pain in young women. This research method uses a quantitative research design with a quasi-experiment method with a two group pre-test and post-test design. Results achieved based on the research results in the stretching group was 80.0%, and the results of the Pairet Sample t test with a P value of 0.004 < 0.005. Meanwhile, in the warm compress group, it was 86.7% with Pairet Sample t test results with P Value 0.000 < 0.005. The conclusion of the research shows that there is an influence of the effectiveness of abdominal stretching exercises and warm compresses on dysmenorrhea pain in young women at MTS Tanwiriyyah Cianjur in 2022.